Oxidative stress is the common causal link between renal stones and diabetes mellitus in adult people - Tayyab Uddin Khand; Naseem Aslam Channa; Khand, Fatehuddin (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the common risk factors involved in the pathogenesis of renal stones and diabetes mellitus in adults. Method: The case-control study was carried out at the urology outpatient department and diabetic clinic of the Liaquat University of Medical and Health Sciences, Hyderabad, Pakistan, from January 2019 to January 2020, and comprised renal stone patients in group A, diabetes mellitus patients in group B and healthy controls in group C. Height and weight were determined for all subjects, followed by calculation of body mass index. Serum samples were analysed for creatinine, uric acid, total antioxidants, iron, malondialdehyde, superoxide dismutase, catalase, glutathione peroxidase, lactate dehydrogenase, xanthine oxidase, C-reactive protein, and nuclear factor kappa-light-chain-enhancer of activated B cells. Intra-group comparisons were done. Data was analysed using SPSS 22. Results: Of the 400 subjects, 100(25%) each were in groups A and B, and 200(50%) were in group C. Overall, there were 236(59%) males and 164(41%) females. The age range of the sample was 20-40 years. Obesity was more prevalent in group B 26(26%) as against 4(4%) in group A and 20(10%) in group C. Compared to group C, superoxide dismutase (p=0.0128) and C-reactive protein (p=0.032) levels were higher in group B, while the levels were lower for uric acid (p=0.0067), iron (p=0.0147) and xanthine oxidase (p=0.0360). —Continue